Characteristics of patients with violent recidivism in the forensic mental health system in Japan - Koike, Junko (The journal of forensic psychiatry & psychology, 2022)
Methods A retrospective study was conducted with patients involuntarily admitted to psychiatric hospitals. Patients were divided into the following two groups based on whether they had a history of legal proceedings before committing the act that subjected them to their current sentence: those who repeatedly harmed others (RHO) and those who did not (NRHO). We compared their characteristics and performed a two-variable logistic regression analysis.Results The total number of patients was 210. The RHO and NRHO groups included 51(24.3%) and 159(75.7%) patients. A comparison between the two groups revealed that patients in the RHO group were overwhelming male, with substance use and intellectual problems. The two-variable logistic regression analysis results indicated that the variables associated with RHO were ”F1” and ”a history of involuntary admission” in order of high odds ratios.Conclusion The essential points regarding support for the RHO group were as follows: (1) intervention at the stages of initial criminal proceedings and involuntary admission, and (2) collaborative support between penal codes and the public health, medical, and welfare systems.